THE INFLUENCE OF COMMITMENT, PRODUCTIVITY, ORGANIZATION CITIZENSHIP BEHAVIOR, TRAINING ON PERFORMANCE POLICE TANJUNGPINANG IN THE TIME OF COVID-19 - Rini Elfina; Rona Tanjung; Mulyadi (International Journal of Social Science, 2022)
This study aims to determine and analyze the effect of commitment, productivity, organizational citizenship behavior, training on the performance of the Tanjungpinang Barat police personnel. The sample used in this study amounted to 30 people, questions were given using a questionnaire distributed through purposive sampling using data analysis methods used were validity test, reliability test, classical assumption test, and multiple regression analysis. In this study, there are five hypotheses presented by the researcher and the analysis mode used in this study is based on data analysis, the results of this study. Based on data analysis, the results of the study show that Commitment (X1) to the Pesonil Polsek Tanjungpinang Barat. Polsek has a positive and significant effect on performance. Productivity (X2) at the Pesonil Polsek Tanjungpinang Barat Polsek has a positive and significant effect on performance. Organization Citizenship Behavior (X3) at the Pesonil Polsek Tanjungpinang Barat Polsek has a positive and significant effect on performance. Training (X3) at the Pesonil Polsek Tanjungpinang Barat Polsek has a positive and significant effect on performance. Commitment (X1), Productivity (X2), Organization Citizenship Behavior (X3), Training (X5) Together or simultaneously have a positive and significant effect on the performance (Y) of West Tanjungpinang Police personnel. Training (X3) at the Pesonil Polsek Tanjungpinang Barat Polsek has a positive and significant effect on performance. Commitment (X1), Productivity (X2), Organization Citizenship Behavior (X3), Training (X5) Together or simultaneously have a positive and significant effect on the performance (Y) of West Tanjungpinang Police personnel. Training (X3) at the Pesonil Polsek Tanjungpinang Barat Polsek has a positive and significant effect on performance. Commitment (X1), Productivity (X2), Organization Citizenship Behavior (X3), Training (X5) Together or simultaneously have a positive and significant effect on the performance (Y) of West Tanjungpinang Police personnel